1993
DOI: 10.1159/000292600
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-drenergic Receptors in Human Myometrium: Changes during Pregnancy

Abstract: Myometrial biopsies from 80 women, delivered by cesarean section in 26–42 completed weeks of pregnancy, were analyzed using radiolabeled Α1-antagonist [3H]-prazosin and Α1-antagonist [3H]-rauwolscine. Statistical analysis was performed using Student’s t test (two-tailed), where p < 0.05 was considered significant. The number of Α2-adrenergic receptors did not vary (mean value weeks 37–39 =17.2 ± 1.3 fmol/mg protein), while the dissociation constant (K Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…The following decrease of choroidal thickness in the third trimester may be related to the peak increase of oestrogen and progesterone concentrations in this period. A significant increase in α 1-adrenoceptor concentrations has been reported in weeks 37–39 of pregnancy, associated with increased oestrogen and progesterone concentrations,18 and vasoconstriction related to the increased adrenoceptor activity in this period can potentially explain the decrease in choroidal thickness detected in our study.…”
Section: Discussionsupporting
confidence: 69%
“…The following decrease of choroidal thickness in the third trimester may be related to the peak increase of oestrogen and progesterone concentrations in this period. A significant increase in α 1-adrenoceptor concentrations has been reported in weeks 37–39 of pregnancy, associated with increased oestrogen and progesterone concentrations,18 and vasoconstriction related to the increased adrenoceptor activity in this period can potentially explain the decrease in choroidal thickness detected in our study.…”
Section: Discussionsupporting
confidence: 69%
“…Dahle et al [34] studied myometrium obtained at cesarean section at various gestational ages and reported that a,ARs were up-regulated in human myometrium near term (37-39 weeks) compared to earlier in the third trimester, No such up-regulation was detected in women who underwent cesarean section at [40][41][42] weeks, and the authors suggested that this group may represent women with a high percentage of dysfunctional labor in whom the uterus was not properly primed for contraction [34]. Breuiller et al [59] have demonstrated that cw2ARs are present in high concentrations and are effective in inhibiting cAMP production in human myometrium at term, in contrast to findings in other species.…”
Section: Uterine Contraction and Labormentioning
confidence: 99%
“…ciARs Postsynaptic a2ARs are found in human and animal myometrium, where they appear to mediate uterine contraction and vasoconstriction by inhibition of adenylyl cyclase and effects on calcium [34]. The human placenta has also been shown to possess functional a2ARs [35].…”
Section: Parsmentioning
confidence: 99%
“…Myometrial relaxation, on the other hand, is mediated by ß 2 -adrenoceptors. Of the ·-adrenoceptors, both the · 1 -and · 2 -adrenoceptors have been demonstrated in the human myometrium [2] and changes in the population have been shown to occur during pregnancy [3]. The predominant adrenoceptor subtype mediating uterine contraction seems to be the · 1 -adrenoceptor, whereas the physiological function of the · 2 -adrenoceptor remains unclear [4].…”
Section: Introductionmentioning
confidence: 99%